Assignment: Area Moment of Inertia
Assignment: Area Moment of Inertia
Assignment: Area Moment of Inertia
Now,
𝐼𝑥 = 𝐼𝑥 + 𝐴1 𝑑1 2 + 𝐼𝑥 + 𝐼𝑥 + 𝐴2 𝑑2 2
1 2 3
1 3 2 1 3 1 3 2
= 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ + 𝑏 ℎ +𝐴 𝑑
12 1 1 1 1 12 2 2 12 3 3 2 2
1 1
= × 4 × (0.5)3 + (4 × 0.5) × (1.625)2 + × 1 × (2.75)3 +
12 12
1
× 4 × (0.5)3 + (4 × 0.5) × (1.625)2 𝑚4
12
𝐼𝑦 = 𝐼𝑦 1 + 𝐼𝑦 2 + 𝐼𝑦 3
1 3 1 3 1 3
= 𝑏 ℎ + 𝑏 ℎ + 𝑏 ℎ
12 1 1 12 2 2 12 3 3
1 1 1
= × 0.5 × 43 + × 2.75 × 13 + × 0.5 × 43 𝑚4
12 12 12
𝑋 =𝐴 1 𝑥 1𝐴+𝐴+𝐴2 𝑥 2+𝐴
+𝐴 3 𝑥 3
𝑌 =𝐴1 𝑦 1𝐴+𝐴 2 𝑦 2 +𝐴 3 𝑦 3
1 +𝐴 2 +𝐴 3
1 2 3
= (4×4)×2+(14×2)×5+(6×6)×9
𝑐𝑚 = (4×4)×12+(14×2)×7+(6×6)×3
(4×4)+(14×2)+(6×6) 𝑐𝑚
(4×4)+(14×2)+(6×6)
192+196+108
= 32+140+324
16+28+36 𝑐𝑚
= 16+28+36
𝑐𝑚
= 6.20 𝑐𝑚
= 6.20 𝑐𝑚
Now,
𝐼𝑥 = 𝐼𝑥 + 𝐴1 𝑑1 2 + 𝐼𝑥 + 𝐴2 𝑑2 2 + 𝐼𝑥 + 𝐴2 𝑑2 2
1 2 3
1 3 2 1 3 2 1 3 2
= 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ +𝐴 𝑑
12 1 1 1 1 12 2 2 2 2 12 3 3 2 2
1 1
= × 4 × (4)3 + (4 × 4) × (5.8)2 + × 2 × (14)3 + (2 × 14) ×
12 12
1
(0.8)2 + ×6× (6)3 + (6 × 6) × (3.2)2 𝑐𝑚4
12
2 2 2
𝐼𝑦 = 𝐼𝑦 1 + 𝐴1 𝑑1 + 𝐼𝑦 2 + 𝐴2 𝑑2 + 𝐼𝑦 3 + 𝐴3 𝑑3
1 3 2 1 3 2 1 3 2
= 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ +𝐴 𝑑
12 1 1 1 1 12 2 2 2 2 12 3 3 3 3
1 1
= × 4 × (4)3 + (4 × 4) × (4.2)2 + × 14 × (2)3 + (2 × 14) ×
12 12
1
(1.2)2 + × 6 × (6)3 + (6 × 6) × (2.8)2 𝑐𝑚4
12
For X: For Y: 𝐴1 = 𝐴2 = 𝐴3 = 𝐴4
𝑏1 = 𝑏2 = 𝑏3 = 1 𝑖𝑛. 𝑏1 = 𝑏2 = 𝑏3 = 1 𝑖𝑛. = 6 × 1 𝑖𝑛.4
𝑏4 = 6 𝑖𝑛. 𝑏4 = 1 𝑖𝑛.
(𝑥1 , 𝑦1 ) = (−3.5,3)
ℎ1 = ℎ2 = ℎ3 = 6 𝑖𝑛. ℎ1 = ℎ2 = ℎ3 = 6 𝑖𝑛. (𝑥2 , 𝑦2 ) = (0,9)
ℎ4 = 1 𝑖𝑛. ℎ4 = 6 𝑖𝑛. (𝑥3 , 𝑦3 ) = (3.5,3)
(𝑥4 , 𝑦4 ) = (0,5.5)
𝑑1 = (5.125 − 3) 𝑖𝑛. 𝑑1 = (3.5 − 0) 𝑖𝑛. (𝑥𝑐 , 𝑦𝑐 ) = (0,5.125)
= 2.125 𝑖𝑛. = 3.5 𝑖𝑛.
𝑑2 = (9 − 5.125) 𝑖𝑛. 𝑑2 = 0 𝑖𝑛.
= 3.875 𝑖𝑛. 𝑑3 = (3.5 − 0) 𝑖𝑛.
𝑑3 = (5.125 − 3) 𝑖𝑛. = 3.5 𝑖𝑛.
= 2.125 𝑖𝑛. 𝑑4 = 0 𝑖𝑛.
𝑑4 = (5.5 − 5.125) 𝑖𝑛.
= 0.375 𝑖𝑛.
First, we need to determine the centroid of the following figure.
𝑋 = 𝐴1 𝑥 𝐴1 +𝐴+𝐴2 𝑥 2+𝐴
+𝐴 3 𝑥 3 +𝐴 4 𝑥 4
+𝐴
𝑌 =𝐴1 𝑦 1 +𝐴 2 𝑦 2 +𝐴 3 𝑦 3 +𝐴 4 𝑥 4
𝐴 +𝐴 +𝐴 +𝐴
1 2 3 4 1 2 3 4
(6×1)×(−3.5)+(6×1)×0+(6×1)×3.5+(6×1)×0 (6×1)×3+(6×1)×9+(6×1)×3+(6×1)×5.5
= (6×1)+(6×1)+(6×1)+(6×1)
𝑖𝑛. = (6×1)+(6×1)+(6×1)+(6×1)
𝑖𝑛.
= −21+0+21+0
6+6+6+6 𝑖𝑛. = 18+54+18+33
6+6+6+6 𝑖𝑛.
= 0 𝑖𝑛. = 5.125 𝑖𝑛.
Now,
𝐼𝑥 = 𝐼𝑥 + 𝐴1 𝑑1 2 + 𝐼𝑥 + 𝐴2 𝑑2 2 + 𝐼𝑥 + 𝐴3 𝑑3 2 + 𝐼𝑥 + 𝐴4 𝑑4 2
1 2 3 4
1 3 2 1 3 2 1 3 2 1 3
= 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ +
12 1 1 1 1 12 2 2 2 2 12 3 3 3 3 12 4 4
𝐴4 𝑑4 2
1 1
= × 1 × (6)3 + (6 × 1) × (2.125)2 + × 1 × (6)3 + (6 × 1) ×
12 12
1 1
(3.875)2 + × 1 × (6)3 + (6 × 1) × (2.125)2 + × 6 × (1)2 +
12 12
(6 × 1) × (0.375)2 𝑖𝑛.4
= 18 + 27.094 + 18 + 90.094 + 18 + 27.094 + 0.5 + 0.844 𝑖𝑛.4
= 199.626 𝑖𝑛.4
𝐼𝑦 = 𝐼𝑦 + 𝐴1 𝑑1 2 + 𝐼𝑦 + 𝐼𝑦 + 𝐴3 𝑑3 2 + 𝐼𝑦
1 2 3 4
1 3 2 1 3 1 3 2 1 3
= 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ + 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ
12 1 1 1 1 12 2 2 12 3 3 3 3 12 4 4
1 1 1
= × 6 × (1)3 + (6 × 1) × (3.5) + 2 × 6 × (1)3 + × 6 × (1)3 +
12 12 12
1
(6 × 1) × (3.5)2 + 12 × 1 × (6)3 𝑖𝑛.4
= 0.5 + 73.5 + 0.5 + 0.5 + 73.5 + 18 𝑖𝑛.4
= 166.5 𝑖𝑛.4
𝑋 = 𝐴 1 𝑥𝐴1 +𝐴 2 𝑥 2 +𝐴 3 𝑥 3
+𝐴 +𝐴
𝑌 =𝐴1 𝑦𝐴1 +𝐴 2 𝑦 2 +𝐴 3 𝑦 3
+𝐴 +𝐴
1 2 3 1 2 3
(5×1)×(−5.5)+(5×2)×0+(5×1)×5.5 (5×1)×2+(5×2)×0+(5×1)×(−2)
= (5×1)+(5×2)+(5×1)
𝑖𝑛. = (5×1)+(5×2)+(5×1)
𝑖𝑛.
= −27.5+0+27.5
5+10+5 𝑖𝑛. = 10+0−10
5+10+5 𝑖𝑛.
= 0 𝑖𝑛. = 0 𝑖𝑛.
Now,
𝐼𝑥 = 𝐼𝑥 + 𝐴1 𝑑1 2 + 𝐼𝑥 + 𝐼𝑥 + 𝐴3 𝑑3 2
1 2 3
1 3 2 1 3 1 3 2
= 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ + 𝑏 ℎ +𝐴 𝑑
12 1 1 1 1 12 2 2 12 3 3 3 3
1 1 1
= × 1 × (5)3 + (5 × 1) × (2)2 + × 10 × (1)3 + × 1 × (5)3 + (5 ×
12 12 12
1) × (2)2 𝑖𝑛.4
= 10.417 + 20 + 0.833 + 10.417 + 20 𝑖𝑛.4
= 61.667 𝑖𝑛4
2 2
𝐼𝑦 = 𝐼𝑦 1 + 𝐴1 𝑑1 + 𝐼𝑦 2 + 𝐼𝑦 3 + 𝐴3 𝑑3
1 3 2 1 3 1 3 2
= 𝑏 ℎ +𝐴 𝑑 + 𝑏 ℎ + 𝑏 ℎ +𝐴 𝑑
12 1 1 1 1 12 2 2 12 3 3 3 3
1 1 1
= × 5 × (1)3 + (5 × 1) × (5.5) + 2 × 1 × (10)3 + × 5 × (1)3 +
12 12 12
(5 × 1) × (5.5)2 𝑖𝑛4
= 0.417 + 151.25 + 83.333 + 0.417 + 151.25 𝑖𝑛.4
= 386.667 𝑖𝑛.4